Age and Knee Osteoarthritis Severity Relationship in Indonesian Secondary Referral Hospital - Panji Sananta; Haidar Abror Firladi; Dhelya Widasmara; Eka Noviya Fuzianingsih (Lambung Mangkurat, 2022)
Osteoarthritis is a chronic joint disease that causes pain, disability, and loss of function. More than 80% of cases of osteoarthritis affect the knee joint. The exact cause of knee osteoarthritis is still unknown, but it is generally associated with aging and obesity. This study aimed to determine the relationship between age and the severity of knee osteoarthritis. This research used a cross-sectional study involving patients who suffered from knee osteoarthritis. Data on gender and the severity of osteoarthritis was collected from medical records. The severity of knee osteoarthritis was assessed using the Kellgren-Lawrence system. The data was analyzed using the Spearman correlation. There were 3 patients (8.1%) in the category of late adulthood, 7 patients (18.9%) in the middle-aged category, 13 patients (35.1%) in the early-onset elderly category, and 14 patients (37.8%) in the elderly. Seven patients (23.7%) suffered from osteoarthritis grade 1, 13 patients (35.1%) had grade 2, 16 patients (43.2%) had grade 3, and one patient had grade 4. The Spearman test showed that there was no significant relationship (p>0.05) between age and the severity of knee osteoarthritis. According to the study's findings, there was no correlation between age and the severity of knee osteoarthritis in women and men patients at Baptis Hospital, Batu City.